Dengue virus infection: Need for appropriate laboratory tests for diagnosis and management of the condition in children during an outbreak - Harshavardhini Palanivel; Shashikala Nair; Anandhalakshmi Subramaniyan; Philip Vivian Joseph Ratnam; Reba Kanungo (Wolters Kluwer Medknow Publications, 2015)
Background: Outbreaks of dengue infection occur in several parts of India with clockwork precision closely related to changing seasons. Most recent outbreak in Puducherry occurred between October 2012 and January 2013, affected a sizable pediatric population. A prospective study was done to characterize the demographic, diagnostic and clinical profile of pediatric patients in a tertiary care center in Puducherry. Materials and Methods: Data of patients serologically positive for either dengue NS1 antigen or anti-dengue IgM antibodies were analyzed. Duration of fever, platelet count, complications, risk factors, morbidity and mortality were analyzed. Results: Among pediatric cases with fever who were screened for NS1/IgM antibody during the recent outbreak, 161 (37.5%) tested positive. NS1 was detected in 85% while 5.5% tested positive for IgM and 3% for IgG. Few (4.9%) tested positive for both NS1 and IgM and 1.2% were positive for both NS1 and IgG. The mean age was 6 years of which 9% were <1-year, the youngest being 1-month old infant. Mean duration of fever was 4 days. Vomiting was associated in 42% of cases. Thrombocytopenia (51%) and hepatomegaly (41%) were two major observations. Among the NS1 positive cases, 49% had thrombocytopenia. IgM alone and NS1 with IgM were associated with thrombocytopenia in 67% and 78% respectively. 14 children had complications of dengue shock syndrome, and four had dengue hemorrhagic fever. Totally, 22 of the children had platelet transfusion. There was no mortality reported among any of these children. Conclusion: Combination of clinical findings and rapid NS1, IgM detection helped in confirming the diagnosis for appropriate management of dengue in children.